Ostreopsis fattorussoi sp. nov. (Dinophyceae), a new benthic toxic Ostreopsis species from the eastern Mediterranean Sea. Issue 6 (19th October 2016) - Accoroni, Stefano; Romagnoli, Tiziana; Penna, Antonella; Capellacci, Samuela; Ciminiello, Patrizia; Dell'Aversano, Carmela; Tartaglione, Luciana; Abboud–Abi Saab, Marie; Giussani, Valentina; Asnaghi, Valentina; Chiantore, Mariachiara; Totti, Cecilia
Abstract : The new benthic toxic dinoflagellate, Ostreopsis fattorussoi sp. nov., is described from the Eastern Mediterranean Sea, Lebanon and Cyprus coasts, and is supported by morphological and molecular data. The plate formula, Po, 3′, 7″, 6c, 7s, 5‴, 2′′′′, is typical for the Ostreopsis genus. It differs from all other Ostreopsis species in that (i) the curved suture between plates 1′ and 3′ makes them approximately hexagonal, (ii) the 1′ plate lies in the left half of the epitheca and is obliquely orientated leading to a characteristic shape of plate 6″. The round thecal pores are bigger than the other two Mediterranean species ( O . cf. ovata and O . cf. siamensis ). O. fattorussoi is among the smallest species of the genus (DV: 60.07 ± 5.63 μm, AP: 25.66 ± 2.97 μm, W: 39.81 ± 5.05 μm) along with O. ovata . Phylogenetic analyses based on the LSU and internal transcribed spacer rDNA shows that O. fattorussoi belongs to the Atlantic/Mediterranean Ostreopsis spp. clade separated from the other Ostreopsis species. Ostreopsis fattorussoi produces OVTX‐a and structural isomers OVTX‐d and ‐e, O . cf. ovata is the only other species of this genus known to produce these toxins. The Lebanese O. fattorussoi did not produce the new palytoxin‐like compounds (ovatoxin‐i, ovatoxin‐j1, ovatoxin‐j2, and ovatoxin‐k) that were previously found in O. fattorussoi from Cyprus. The toxin content was in the range of 0.28–0.94 pg · cell −1 . On the Lebanon coast, O. fattorussoi was recorded throughout the year 2015 (temperature range 18°C–31.5°C), with peaks in June and August.